2019
DOI: 10.1111/jace.16502
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic, piezocatalytic, and piezo‐photocatalytic effects in ferroelectric (Ba0.875Ca0.125)(Ti0.95Sn0.05)O3 ceramics

Abstract: Ba0.875Ca0.125Ti0.95Sn0.05O3 (BCT‐Sn) was examined for photocatalytic, piezocatalytic, and piezo‐photocatalytic effects. BCT‐Sn powder was poled through corona poling and it was found that poling induces significant impact on photocatalysis. This material was also able to degrade dye (Methylene blue) using poled powder under ultrasonication (piezocatalysis). There was a remarkable effect in dye degradation which is a clear indication of the importance of piezocatalytic behavior in catalytic reactions. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 50 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…20 In environment remediation, doping elements like Ca,Zr, and Sr in BaTiO 3 ceramics demonstrated remarkable multicatalytic capabilities. [21][22][23] It should be worth mentioning that effective piezoelectricity can only be seen in ferroelectric materials when all developed dipoles are oriented in a particular direction. Electrical poling is a technique of aligning dipoles in a particular direction of an applied electric field.…”
Section: Introductionmentioning
confidence: 99%
“…20 In environment remediation, doping elements like Ca,Zr, and Sr in BaTiO 3 ceramics demonstrated remarkable multicatalytic capabilities. [21][22][23] It should be worth mentioning that effective piezoelectricity can only be seen in ferroelectric materials when all developed dipoles are oriented in a particular direction. Electrical poling is a technique of aligning dipoles in a particular direction of an applied electric field.…”
Section: Introductionmentioning
confidence: 99%
“…9 The efficiency of a photocatalyst is limited by short carrier diffusion distances and the recombination phenomenon of carriers. 10 ZnO is among the most appealing semiconductor photocatalysts for degrading organic contaminants, because of its ease of preparation, cost-effectiveness, low toxicity, excellent stability, and powerful redox potential. ZnO shows poor utilization of solar energy in photocatalytic activity due to its large bandgap (3.20 eV).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in piezoelectric materials with photocatalytic activity, the polarization can enhance the charge energy shifting or photoexcited electron/hole transfer, resulting in the excellent catalytic activity. [ 15,16 ] Some classical piezoelectric materials, such as ZnO, [ 17 ] BaTiO 3 , [ 18,19 ] and BiFeO 3 , [ 20 ] have efficiently demonstrated the abovementioned piezocatalytic behaviors. Wang et al reported an excellent decomposition of organic dyes achieved by piezocatalysis using BaTiO 3 nanoparticles under ultrasonic vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in piezoelectric materials with photocatalytic activity, the polarization can enhance the charge energy shifting or photoexcited electron/hole transfer, resulting in the excellent catalytic activity. [15,16] Some classical piezoelectric materials, such as ZnO, [17] BaTiO 3 , [18,19]…”
mentioning
confidence: 99%